STIMULASI KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN MELALUI KEGIATAN MENGGAMBAR BEBAS DENGAN TEKNIK GRAFITO - Cindy Elsya Ramadhani; Nyimas Muazzomi; Winda Sherly Utami (STKIP Pesisir Selatan, 2026)
This study aims to determine the effect of free drawing using the grafito technique on the speaking ability of children aged 5-6 years at KB Kasih Ibu Muara Bahar. This research uses a quantitative approach with a pre-experimental method, specifically the One Group Pretest-Posttest design. The population in this study were all children aged 5-6 years at KB Kasih Ibu Muara Bahar, totaling 23 children, and the entire population was used as the sample (total sampling). Data collection techniques used observation. The research instrument was an observation sheet based on indicators of speaking ability according to Permendikbud No. 137 of 2014. Data analysis techniques included normality test, homogeneity test, and hypothesis testing using paired sample t-test. The results showed that the average pretest score was 14.61 (36.52%) and the average posttest score was 28.13 (70.33%). The hypothesis test results obtained a Sig. (2-tailed) value of 0.000 < 0.05, so H0 was rejected and Ha was accepted. The effect size calculation using Cohen's d obtained a value of 4.97, which is included in the strong effect category. Thus, it can be concluded that there is a significant influence of free drawing using the grafito technique on the speaking ability of children aged 5-6 years at KB Kasih Ibu Muara Bahar